2013
DOI: 10.4187/respcare.02568
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Nasal and Laryngeal Airways in Children: Implications in Breathing and Inhaled Aerosol Dynamics

Abstract: BACKGROUND:The human respiratory airway undergoes dramatic growth during infancy and childhood, which induces substantial variability in air flow pattern and particle deposition. However, deposition studies have typically focused on adult subjects, the results of which cannot be readily extrapolated to children. We developed models to quantify the growth of human nasallaryngeal airways at early ages, and to evaluate the impact of that growth on breathing resistance and aerosol deposition. METHODS: Four image-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 35 publications
2
57
0
1
Order By: Relevance
“…1 In vivo comparative studies evaluating aerosol deposition within different regions of the human respiratory tract in infants, young children, and adults are lacking. A recent study 2 evaluating drug deposition using a 3-dimensional model rendering from computed tomography scans of healthy infants, children, and adults showed that substantial variability exists in airway morphology, air-flow dynamics, and regional aerosol deposition among subjects of different ages.…”
Section: Differences In Aerosol Drug Delivery Between Pediatric and Amentioning
confidence: 99%
See 2 more Smart Citations
“…1 In vivo comparative studies evaluating aerosol deposition within different regions of the human respiratory tract in infants, young children, and adults are lacking. A recent study 2 evaluating drug deposition using a 3-dimensional model rendering from computed tomography scans of healthy infants, children, and adults showed that substantial variability exists in airway morphology, air-flow dynamics, and regional aerosol deposition among subjects of different ages.…”
Section: Differences In Aerosol Drug Delivery Between Pediatric and Amentioning
confidence: 99%
“…Younger patients have smaller nostrils, a shorter turbinate region, a narrower nasopharynx, a narrower pharynx-larynx, and a relatively larger anatomic dead space than do adults, making drug delivery a challenge. 2 Nasal airway resistance accounts for nearly half of the respiratory resistance in healthy infants, 3 and turbulent flow in this region likely accounts for a large amount of impactive drug loss in the upper airways. Interestingly, nasal breathing for aerosol delivery to the distal airways is similar to, or more efficient than, mouth breathing in infant and toddler models, 4 contrary to what is observed in older children and adults, who have more well-developed nasal turbinates and less complex airway structures.…”
Section: Differences In Aerosol Drug Delivery Between Pediatric and Amentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistent changes in nasal patency occur at the same time as the most significant somatic growth, changes in nasal and orofacial morphology, and development of the permanent dentition. 17,[28][29][30] Among changes in size and shape of the respiratory and vocal tracts, laryngeal descent, associated with hyoideal descent, is greater in males, resulting in relatively longer airways. 31,32 No gender differences in nasal resistance have been found for children, 13,14,16 while Kim et al 23 reported lower resistance for females and also a decrease in resistance with age among adults.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years, anatomically correct airway models have been used in an attempt to provide a more realistic evaluation of the drug output of a device under specific breathing conditions. [104][105][106] One area of significant concern is the fact that each laboratory, either academic or industry-affiliated, has developed its own model, making data comparison across laboratories very difficult.…”
Section: Comparison Of New and Existing Technologiesmentioning
confidence: 99%